Impacts of human habitat development on the environment – challenges and the way forward - Chan, Ngai Weng (Environmental Management Society, Malaysia, 2010)
Ever since homo sapiens appeared on earth some 2.5 million years ago, their need to build human habitats have impacted upon the environment. Early homo sapiens were largely constrained by Environmental Determinism which did little harm to the environment. However, Possibilism and Human Determinism of the modern era left inerasable scars on earth. Increasingly, as humans advanced in science and technology, and preferred to live in urban habitats, they have inadvertently impacted upon the environment very significantly, often to the point of irreversible damage. Modern humans and the construction of their habitats have significantly impacted upon and changed the environment as follows: changed the atmospheric characteristics resulting in climate change (initially at the local level but now globally); changed the hydrological characteristics resulting in floods, droughts, water crises and other hydrological disasters; changed the lithospheric characteristics resulting in soil erosion, landslides and other mass movements; changed the biosphere resulting in loss of natural habitats (of indigenous people, flora and fauna); and changed the cryosphere resulting in global melting and retreating of ice shelves and ice sheets leading to sea level rise and a host of other environmental disasters. However, a combination of realisation of environmental degradation, the environmental movement, and the rise of sustainable development have led to environmentally-friendly human habitats. To achieve sustainable development in human habitats, humans need to control urban growth, control population growth, illegal immigrants and proliferation of slums, ensure adequate (quantity) and appropriate (quality) housing, institute legislation for disaster-resistant habitat structures, develop technology for early warning system of major risks to habitats, and mobilise politicians to commit to environmental management of human habitats vis-à-vis economic development. Most of all, future human habitats should be modelled and developed as “eco-habitats”